Nyerere Freedom and Unity - Nyerere,Julius K. (London Oxford University Press, 1974)
As with the previous volumes, Freedom and Unity/Uhuru na Umoja and Freedom and Socialism Uhuru na Ujama, it is a representative sample of Tanzania's and her leader's, views on such subjects as socialism, economic policy, human equality,African Unity and liberation and International relations.However president Nyerere emphasizes in the preface, that except where specifically mentioned these statements are not a description of what now exists in Tanzania or in Africa, but rather of what is beginning aimed at.The is a description of goals and facts, and the ideas of the author are intended as a contribution towards the achievement of those goals This, the third major collection of president Julius Nyerere's speeches and writings, covers the period January 1968 to january 1973. As with the previous volumes, Freedom and Unity/Uhuru na Umoja and Freedom and Socialism Uhuru na Ujama, it is a representative sample of Tanzania's and her leader's, views on such subjects as socialism, economic policy, human equality,African Unity and liberation and International relations.However president Nyerere emphasizes in the preface, that except where specifically mentioned these statements are not a description of what now exists in Tanzania or in Africa, but rather of what is beginning aimed at.The is a description of goals and facts, and the ideas of the author are intended as a contribution towards the achievement of those goals
Keywords: politics and Government